1997
DOI: 10.1079/pns19970060
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid supply and metabolism by the ruminant mammary gland

Abstract: Metabolism in the gastrointestinal tract ) and liver (Lobley & Milano, 1997) has been shown to be important in determining the amount and pattern of amino acids (AA) available post-hepatically for mammary gland utilization as well as for muscle, skin and, indeed, the gastrointestinal tract. High rates of metabolism by the non-mammary tissues have been suggested as one reason for the low efficiency (approximately 20 %) of conversion of dietary N into milk protein . Thus, ways to reduce these losses could lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 40 publications
1
25
0
1
Order By: Relevance
“…This suggests that supplemented Phe did not provide an additional supply of AA, but rather replaced peptides as the source of Phe to support milk protein synthesis (Bequette and Backwell, 1997). It is also possible that, due to the relatively high MCP flow in our study and the large contribution of MCP to total absorbable protein, any benefit that resulted from supplementation of Phe alone was too small to be measured (Robinson, 2010).…”
Section: Discussionmentioning
confidence: 52%
“…This suggests that supplemented Phe did not provide an additional supply of AA, but rather replaced peptides as the source of Phe to support milk protein synthesis (Bequette and Backwell, 1997). It is also possible that, due to the relatively high MCP flow in our study and the large contribution of MCP to total absorbable protein, any benefit that resulted from supplementation of Phe alone was too small to be measured (Robinson, 2010).…”
Section: Discussionmentioning
confidence: 52%
“…27). In addition, dairy cows have a relatively low efficiency (ϳ25-30%) in the transformation of dietary nitrogen into milk proteins (23), with a high rate of protein turnover (22). In the goat mammary gland, the daily tissue protein synthesis (i.e., nonmilk protein in mammary tissue) can account for as much as 88% of the total protein synthesized, which represents half of the available ATP supply generated in the lactating udder (86).…”
Section: Regulation Of Protein Synthesis By the Energy Content In Thementioning
confidence: 99%
“…-S1 -Lactalbumin [64] for pig, [10] for goat, and [65] for mouse. For cows and goats it has been reported that the protein synthesis in mammary gland is between 1.3 to 2.5 the rate of milk protein secretion [12,66]; thus, for cow an average of 2.0 was used. $ Mammary Gland (MG).…”
Section: Transcriptomics: a Novel Approach To Study Biologymentioning
confidence: 99%